Significantly Enhanced Power Generation from Extremely Low‐Intensity Magnetic Field via a Clamped‐Clamped Magneto‐Mechano‐Electric Generator. Issue 10 (24th January 2022) - Chu, Zhaoqiang; Sun, Zechen; Wang, Bo; Song, Kaixin; Wang, Jiazeng; Gao, Junqi; Dong, Shuxiang
Abstract: A magneto‐mechano‐electric (MME) generator that can harvest ambient magnetic noise plays a significant role in powering Internet of Things (IoT) sensor networks. However, it is still a challenge to capture sufficient energy and continuously drive IoT nodes from extremely low‐intensity magnetic noise below 1 Oe. To circumvent the close dependence of the resonant frequency on the magnetic proof mass in conventional MME generators, a new clamped‐clamped (C‐C) MME generator is proposed, that allows a much heavier magnetic mass to be attached at the beam center. Under weak magnetic fields of 0.48 and 0.96 Oe at 50 Hz, optimized output powers of 370 and 970 μWRMS, respectively are achieved, which shows an enhancement of ≈120% over that of cantilevered MME generators. The underlying mechanics are theoretically revealed by comparing the lumped parameters with a cantilevered MME generator and by calculating their deflection gain. Finally, it is demonstrated that the harvested energy from the proposed C‐C MME generator from a 0.48 Oe magnetic field at 50 Hz is sufficient to continuously drive an IoT sensor without any additional intervals for recharging. It is believed that this work will open new possibilities for designing MME generators suitable for weak field energy harvesting. Abstract : A new clamped‐clamped magneto‐mechano‐electric generator that can break the mutual dependence of the resonant frequency and the magnetic mass is developed to allow a heavier magnetic mass to be attached at the beam center and thus to realize enhanced power generation under low‐range magnetic field excitation (<1 Oe). Experimental results show optimized output power of 370 and 970 μWRMS is realized under weak magnetic fields of 0.48 and 0.96 Oe at 50 Hz, respectively.